(untitled) (Gaceta Técnica, 2023)
The scientific journal Gaceta Técnica, considering the recommendations of the different evaluating entities, has been improving the publication process in order to optimize editorial quality, thus reaching a place in the SciELO Multidisciplinary Repository in 2022, which allows the preservation and dissemination of articles approved for publication in Gaceta Técnica on a larger scale